2022
DOI: 10.1111/anae.15583
|View full text |Cite
|
Sign up to set email alerts
|

Chronic subdural haematoma: the role of peri‐operative medicine in a common form of reversible brain injury

Abstract: Epidemiological studies project a significant rise in cases of chronic subdural haematoma over the next 20 years. Patients with this condition are frequently older and medically complex, with baseline characteristics that may increase peri-operative risk. The intra-operative period is only a small portion of a patient's total hospital stay, with a majority of patients in the United Kingdom transferred between institutions for their surgical and rehabilitative care. Definitive management remains surgical, but p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…A multicentre RCT investigating the use of dexamethasone in patients with chronic subdural haematoma was identified during the review process [36]. The management of this condition is covered in a separate review article in this supplement [37] and therefore the study by Hutchinson et al. [36] is discussed only briefly.…”
Section: Steroidsmentioning
confidence: 99%
“…A multicentre RCT investigating the use of dexamethasone in patients with chronic subdural haematoma was identified during the review process [36]. The management of this condition is covered in a separate review article in this supplement [37] and therefore the study by Hutchinson et al. [36] is discussed only briefly.…”
Section: Steroidsmentioning
confidence: 99%
“…This is especially true given that the many of outcomes measured, such as hospital stay, neurological recovery and discharge destination, can only be measured days to weeks after a relatively short period of anaesthesia. To improve the peri‐operative management of patients with CSDH, we need to move towards delivery of a standardised care package, such as that in place for patients with hip fracture [22], which encompasses the entirety of the patient's hospital stay [5]. Anaesthetic technique may be an important part of this type of care bundle but is unlikely to demonstrate improvements in patient‐centred outcomes if delivered in isolation.…”
Section: Patient Managementmentioning
confidence: 99%
“…These have been discussed in detail in a recent review article and include: the precise role of surgical management; parallel medical treatment (e.g. steroids); pre-optimisation of patients; and the optimal rehabilitation pathway [5]. Anaesthetic technique is one area that may also influence outcomes.…”
mentioning
confidence: 99%
“…In practice, the provision of surgical treatment is complicated. 21 CSDH predominantly affects frail, older patients with comorbidity. 13 Observational studies of routine care have demonstrated high peri-operative morbidity, associated with increased length of stay and approximately 10% mortality at one year.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the tertiary nature of neurosurgical services, care pathways require communication between multiple communities and hospital providers, which is associated with logistical challenges. Developing a framework to maximise the evidenced bene ts of surgery is, therefore, a pressing requirement for routine care, 21 particularly given the estimated 20-50% increase in operative demand by 2050. 17,18 Experience from surgery in the context of frailty has shown that optimised perioperative management has the potential to reduce practice variation and improve surgical outcomes 10 with hip fracture 11 and emergency laparotomy 12 being two notable examples.…”
Section: Introductionmentioning
confidence: 99%